Language internationalization (how english and mandarin become international language) - Marlina Tampubolon; Dwi Pebrina Sinaga; Nurul Husnah Harahap (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The aim of this research is to analyse how English and Mandarin as International Language. This research is descriptive qualitative method. Data was collected through investigation, questionnaire and interview. Based on the research result. It can be conclude that English and Mandarin have been used in the world.  China and the US, moving beyond their influence globally to what may be the most likely situation in the next decade: China and the US, and Chinese and the English as the two most global languages. In this paper, the writers have discussed about how English and China language” Mandarin”. The writers considered the political and ideological contexts to influence English and Mandarin spread and examined as the international language.